Analisis Faktor-Faktor Yang Memengaruhi Minat Pemain Dalam Permainan MOBA (Studi Kasus: Mobile Legends: Bang-Bang!) - I Ketut Sidharta Yogatama; Agi Putra Kharisma; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Mobile Legends: Bang! is a mobile game with the online Multiplayer Battle Arena genre. This game has been downloaded 35 million times and there are 8 million daily active users in Indonesia in December 2017. In July 2018 this game has been downloaded 100 million times and has 43 million active users in Southeast Asia, 50 percent of which come from Indonesia. To find out the reason behind the number of active players in the game Mobile Legends: Bang !, data collection is needed in order to be able to do analysis on players that are divided into 2 groups. The first group, those who play Mobile Legends: Bang! and have never played another MOBA game. The second group, namely people who play Mobile Legends: Bang! and have played other MOBA games. The process of collecting data uses a mixed method consisting of 2 techniques, namely quantitative questionnaires and qualitative interviews based on game design factors. After collecting data, the analysis will be carried out to find out the significant difference in the average value of the questionnaire between the groups and find out the relationship between the value of the questionnaire and the results of interviews so that conclusions can be obtained. The results of the questionnaire analysis between the two groups produced 32 items that did not have a significant difference and 3 items that had significant differences. While the results of interviews from respondents prove that game-design factors have a relationship with the number of active players in the game Mobile Legends: Bang!